(untitled) (Eurasian Journal of Philology Science and Education, 2016)
International lexis has an important place by the degree of the abundance both in English and Russian and their translation has its own peculiarities. International words are the words which have similar form and some analogous meanings in different languages. It is a result of accidental coincidences and mutual influences. International words are known to appear in one or another language either due to borrowing from other languages or when two given languages have borrowed a corresponding word from some third language (for instance, Latin or Greek). For example, the words: ассumulator, alpha, benzol, billiards, bulldog, cafeteria, caravan, chaos, economic, electric, element, energy, film, kodak, legal, minimum, philosopher are generally comprehensible words not only for English speakers but for the speakers of other languages. This is achieved by the international character of the given words.